Measurement of Trust in Automation: A Narrative Review and Reference Guide - Kohn, Spencer C.; de Visser, Ewart J.; Wiese, Eva; Lee, Yi-Ching; Shaw, Tyler H. (Frontiers in Psychology, 2021)
With the rise of automated and autonomous agents, research examining trust in automation has attracted considerable attention over the last few decades. Trust is a rich and complex construct which has sparked a multitude of measures and approaches to study and understand it. This comprehensive narrative review addresses known methods that have been used to capture trust in automation. We examined measurements deployed in existing empirical works, categorized those measures into self-report, behavioral and physiological indices, and examined them within the context of an existing model of trust. The resulting work provides a reference guide for researchers, providing a list of available trust in automation measurement methods along with the model-derived constructs that they capture including judgements of trustworthiness, trust attitudes and trusting behaviors. The article concludes with recommendations on how to improve the current state of trust in automation measurement.